The decline of the lanner falcon in Mediterranean landscapes: competition displacement or habitat loss?. (6th July 2018) - De Rosa, D.; Di Febbraro, M.; De Lisio, L.; De Sanctis, A.; Loy, A.
Abstract: The peregrine falcon has shown an increasing tendency to replace the lanner falcon at its breeding sites in the Mediterranean area. This has been suggested as the main cause of the reduction in the distribution of the lanner observed in central Italy. We focused on these two falcon species to disentangle the relative contribution of habitat filtering and biotic interactions on the co‐occurrence of their breeding sites. We hypothesized that the replacement of lanner breeding sites with peregrine falcon breeding sites is due to competitive exclusion rather than to environmental factors, and predicted how land‐use change might affect falcon species distributions and biotic interactions. To test our hypothesis, we proposed a modelling framework including niche overlap tests, Bayesian co‐occurrence analysis and species distribution models (SDMs). A significant niche similarity emerged between the breeding sites used exclusively by peregrine or lanner falcons, and those used by both species. Bayesian co‐occurrence analysis showed that biotic interactions significantly explained the negative co‐occurrence between the two falcon species. SDMs predicted that land‐use change would reduce suitable breeding habitats exclusive of each species as well as those suitable for both falcons. Results of niche overlap and co‐occurrence analysis provided strong support for the hypothesis of competitive interaction for breeding sites between peregrine and lanner falcons in central Italy. The out‐competed lanner falcon would be displaced from optimal habitats by the peregrine and forced to exploit suboptimal habitats to minimize competition. While competition with the peregrine may represent a threat for the lanner in the short term, habitat loss due to land‐use change will pose a more severe threat for the long‐term persistence of lanner falcon in central Italy. Abstract : The peregrine falcon has shown an increasing tendency to replace the lanner falcon at its breeding sites in the Mediterranean area. This has been suggested as the main cause of the reduction in the distribution of the lanner observed in central Italy. We hypothesised that the replacement of lanner breeding sites by peregrine falcon is due to competitive exclusion rather than to environmental factors. Moreover, we investigated how land‐use change might affect falcon species distributions and biotic interactions. Our results provided strong support for the hypothesis of competitive interaction for breeding sites between peregrine and lanner falcons in central Italy. In addition, while competition with the peregrine may represent a threat for the lanner in the short term, habitat loss due to land‐use change will pose a more severe threat for lanner falcon long‐term persistence in central Italy. Photo credit: Stig Frode Olsen.